1996
DOI: 10.1046/j.1365-2141.1996.d01-1864.x
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin production by interstitial cells of hypoxic monkey kidneys

Abstract: Previous studies which demonstrated that interstitial cells of the peritubular capillary bed of the kidneys are the site of erythropoietin (Epo) production have been performed in non-primate species. In this study, kidneys from adult rhesus monkeys exposed to 18 h hypoxia (0.42 atm) with high serum (5685 mU/ml) and kidney (814 mU/g. includes serum EPO in the kidney) levels of Epo were compared with a kidney from a nonhypoxic normal rhesus monkey. Localization of Epo mRNA by in situ hybridization was carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
0
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(49 citation statements)
references
References 21 publications
2
44
0
3
Order By: Relevance
“…Previous studies of renal EPO-producing cells have suggested other sites of EPO synthesis including peritubular interstitial cells and capillaries. 20,[27][28][29] The detection of EPO mRNA in proximal tubule cells after hypoxia agrees with others. [30][31][32][33] Lack of EPO signal in normoxia and its sharp localization in hypoxia support the specificity of our ISH technique.…”
Section: Discussionsupporting
confidence: 78%
“…Previous studies of renal EPO-producing cells have suggested other sites of EPO synthesis including peritubular interstitial cells and capillaries. 20,[27][28][29] The detection of EPO mRNA in proximal tubule cells after hypoxia agrees with others. [30][31][32][33] Lack of EPO signal in normoxia and its sharp localization in hypoxia support the specificity of our ISH technique.…”
Section: Discussionsupporting
confidence: 78%
“…More recently, several investigators demonstrated EPO mRNA localized only in peritubular capillary beds of hypoxic kidneys (9,13). Still others have demonstrated EPO synthesis in interstitial cells of peritubular capillaries (16). In our study, staining clearly demonstrated specific immunoreactivity only in proximal tubule cells of rat kidneys as confirmed by hematoxylin-eosin staining in parallel sections.…”
Section: Discussionsupporting
confidence: 58%
“…1,2 As a secreted monomeric sialoglycoprotein, EPO then targets developing erythroblasts, and is essential for red cell formation during definitive bone marrow and fetal liver erythropoiesis. [3][4][5][6][7][8] Prospective roles for EPO in promoting primitive red cell formation in yolk sac also have recently been described.…”
Section: Introductionmentioning
confidence: 99%